Laboratory Electrical Conductivity of Marine Gas Hydrate. Issue 16 (20th August 2020) - Constable, Steven; Lu, Ryan; Stern, Laura A.; Du Frane, Wyatt L.; Roberts, Jeffery J.
Abstract: Methane hydrate was synthesized from pure water ice and flash frozen seawater, with varying amounts of sand or silt added. Electrical conductivity was determined by impedance spectroscopy, using equivalent circuit modeling to separate the effects of electrodes and to gain insight into conduction mechanisms. Silt and sand increase the conductivity of pure hydrate; we infer by contaminant NaCl contributing to conduction in hydrate, to values in agreement with resistivities observed in well logs through hydrate‐saturated sediment. The addition of silt and sand lowers the conductivity of hydrate synthesized from seawater by an amount consistent with Archie's law. All samples were characterized using cryogenic scanning electron microscopy and energy dispersive spectroscopy, which show good connectivity of salt and brine phases. Electrical conductivity measurements of pure hydrate and hydrate mixed with silt during pressure‐induced dissociation support previous conclusions that sediment increases dissociation rate. Plain Language Summary: Methane hydrate is a frozen mixture of methane gas and water ice and occurs naturally in the seafloor of the continental shelves worldwide. Hydrate is variously considered a source of energy, a natural hazard, or a potential contribution to ocean acidification and climate change. Measurement of seafloor electrical conductivity, either using borehole logs or geophysical prospecting methods, is one of the most reliable ways of estimating hydrate location and abundance, but such methods need to be calibrated using laboratory measurements on hydrate‐sediment mixtures. We have made laboratory conductivity measurements on mixtures of hydrate, sand and silt, and seawater. Our results are in good agreement with borehole logs through seafloor sediments fully saturated with hydrate and will allow other scientists to more reliably estimate hydrate concentration from electrical conductivity. Key Points: We quantified the electrical conductivity of laboratory‐formed methane hydrate mixed with sand or silt plus a fluid phase Conductivity measurements of hydrate and sand agree with borehole logs through highly saturated hydrate Hydrate saturation in our samples is consistent with a simple version of Archie's law